Molecular dynamics simulation of carbon dioxide flow in kaolinite pores - Sun, Zhigang; Yang, Tianfang; Jiang, Wenyin (Frontiers in Energy Research, 2024)
Abstract：In order to estimate the effective storage capacity of carbon dioxide in geological storage, it makes great significance to understand the seepage mechanism of flowing carbon dioxide fluid and its influence on the occurrence state in micropore. In this paper, the molecular simulation method was used to obtain the optimal configuration of kaolinite micropore and carbon dioxide molecules. The molecular dynamics method was used to simulate the flow characteristics of carbon dioxide fluid in kaolinite pores in differential depth of burial under constant pressure drop. The results show that the adsorption capacity of carbon dioxide fluid on the wall of kaolinite decreases with the increase of burial depth, the fluid density in the center of the micropore increases with the increase of burial depth, the diffusion capacity of the fluid changes significantly when the burial depth is greater than 2km; when a constant differential pressure is applied, the flow of carbon dioxide fluid in the pore conforms to the classical poiseulle flow, the diffusion ability of the fluid increases with the increase of burial depth ,nearly doubling, and the slip length also increases with the increase of burial depth; the flow behavior significantly reduces the total amount of carbon dioxide in kaolinite micropore, where the density of the first adsorption layer near the wall decreases by at least 20%, and its effect on fluid is greater than that caused by the increase of burial depth. Therefore, when estimating the effective storage capacity of carbon dioxide in geological storage, the influence of pressure drop and burial depth on the total reduction of geological sequestration should be considered at the same time. The purpose is to provide more detailed theoretical basis for carbon dioxide geological sequestration.